Technologies used in underground mining Mines of Peru - De la Cruz Carrasco, Estanislao (1998)
In this article we publish the cutting and down-filling methods that the exploitation technology uses in the underground mines of Peru. It describes in which cases it is applied, the types of deposits, the behavior of the mineral and the boxes, the development and preparation for the application of the method. In the break within the stope (cutting), the drilling meshes that are applied for each method, the drilling equipment, and the material with their respective blasting accessories are described; as well as the benefits and drawbacks of this method. Finally, the recovery of the mineral from the exploitation block, the efficiency and variations of the method, and the mention of the mines in which they are applied in Peru are described.